Perception of Distance Learning in Bangladeshi Tertiary Education: Prospects and Obstacles in the Covid-19 Era - S. M. Sabbih Hossain; Md. Rahat Khan (Journal of Social, Humanity, and Education, 2021)
Purpose: The key purpose of the study is to understand the university students' perception of a sudden distance learning platform from Bangladesh (a least developed countries' perspective). Methodology: This particular study has employed a qualitative research method with the support of interview and observation methods. The study has selected 20 University students as a sample size based on purposive sampling. Results: The findings provide a vivid outline of the current situation of the universities- that the students have- over the influence of distance learning on education, technology, their university, course instructors, and themselves. Conclusions: This study examines Least Developed Countries (LDC) students’ perceptions of distance learning, highlighting adaptability opportunities and recommendations to improve quality and reduce barriers. Limitations: The data was qualitative in nature and the study only interviewed the university students but not the other stakeholders of that system; in addition, the study did not triangulate the data with more quantitative data. Contributions: The study contributes to literature on university education in LDC and benefits higher education institutions facing distance learning prospects and obstacles during and after COVID-19.